Cloning of a creatinase gene from Pseudomonas putida in Escherichia coli by using an indicator plate. - Chang, M C (1992)
A genomic library of Pseudomonas putida DNA was constructed by using plasmid pBR322. Transformants of Escherichia coli in combination with Proteus mirabilis cells grown on creatinase test plates were screened for creatinase activity; transformants were considered positive for creatinase activity if a red-pink zone appeared around the colonies. One creatinase-positive clone was further analyzed, and the gene was reduced to a 2.7-kb DNA fragment. A unique protein band (with a molecular weight of approximately 50,000) was observed in recombinant E. coli by minicell analysis.